The Development and Evaluation of a Novel Highly Selective PET Radiotracer for Targeting BET BD1 - Yanli Wang; Yongle Wang; Yulong Xu; Leyi Kang; Darcy Tocci; Changning Wang (MDPI AG, 2024)
Background/Objectives: Small molecules that interfere with the interaction between acetylated protein tails and the tandem bromodomains of BET (bromodomain and extra-terminal) family proteins are pivotal in modulating immune/inflammatory and neoplastic diseases. This study aimed to develop a novel PET imaging tracer, [11C]GSK023, that targets the N-terminal bromodomain (BD1) of BET family proteins with high selectivity and potency, thereby enriching the chemical probe toolbox for epigenetic imaging. Methods: [11C]GSK023, a radio-chemical probe, was designed and synthesized to specifically target the BET BD1. In vivo PET imaging evaluations were conducted on rodents, focusing on the tracer's distribution and binding specificity in various tissues. Blocking studies were performed to confirm the probe's selectivity and specificity. Results: The evaluations revealed that [11C]GSK023 demonstrated good uptake in peripheral organs with limited brain penetration. Further blocking studies confirmed the probe's high binding specificity and selectivity for the BET BD1 protein, underscoring its potential utility in epigenetic imaging. Conclusions: The findings suggest that [11C]GSK023 is a promising PET probe for imaging the BET BD1 protein, offering the potential to deepen our understanding of the roles of BET bro-modomains in disease and their application in clinical settings to monitor disease progression and therapeutic responses.